Association of Vitamin E with Rapid Thawing on Goat Semen. (11th May 2014) - Penitente-Filho, Jurandy Mauro; Oliveira, Fabrício Albani; Jimenez, Carolina Rodriguez; Carrascal, Erly; Dias, Júlio César Oliveira; Oliveira, Gisele Dias; Silveira, Renata Gomes; Silveira, Camila Oliveira; Torres, Ciro Alexandre Alves
Abstract : The aim of this study was to evaluate the effects of vitamin E associated with rapid thawing on cryopreserved goat semen. Two bucks were used and eight ejaculates per animal were collected using artificial vagina. Semen was diluted with the following treatments: BIOXCELL (control), BIOXCELL + Equex (sodium lauryl sulphate) and BIOXCELL + vitamin E 100  μ M. Semen was packaged into 0.25 mL straws and cooled at 5°C for 1 hour. Freezing was performed in liquid nitrogen vapor (−155°C) during 15 minutes. Then, the straws were immersed in liquid nitrogen (−196°C). Straws were thawed at 38°C/60 seconds or at 60°C/7 seconds with immediate sperm analysis. Hypoosmotic swelling test was performed adding a 20  μ L aliquot of thawed semen to 1 mL of hypoosmotic solution (100 mOsm·Kg −1 ) followed by incubation during 60 minutes in water bath (38°C). Vitamin E did not affect any studied parameters (P > 0.05 ). Nevertheless, defrosting rate of 60°C/7 seconds improved sperm membrane functional integrity (P < 0.05 ). Current knowledge about goat semen cryopreservation is not sufficient to ensure high post-thawing recovery rates; thus, this study brings important data about using antioxidants and different thawing rates on cryopreservation process.